Catalytic epoxidation by perrhenate through the formation of organic-phase supramolecular ion pairs. Issue 16 (26th January 2015) - Cokoja, Mirza; Markovits, Iulius I. E.; Anthofer, Michael H.; Poplata, Saner; Pöthig, Alexander; Morris, Danny S.; Tasker, Peter A.; Herrmann, Wolfgang A.; Kühn, Fritz E.; Love, Jason B.
Abstract : Organic-phase supramolecular ion pair (SIP) host–guest assemblies of perrhenate anions (ReO4 − ) with ammonium amide receptor cations are reported. Abstract : Organic-phase supramolecular ion pair (SIP) host–guest assemblies of perrhenate anions (ReO4 − ) with ammonium amide receptor cations are reported. These compounds act as catalysts for the epoxidation of alkenes by aqueous hydrogen peroxide under biphasic conditions and can be recycled several times with no loss in activity.